Concordance and Acceptability of HPV DNA Genotyping Test by Patient’s Self-Sampling Against Clinician Sampling - Indarti, Junita; Syaharutsa, Danny Maesadatu; Surya, Ilham Utama; Alda, Kristian (Indonesian Socety of Obstetrics and Gynecology, 2024)
Objectives: To determine the effectiveness of this alternative method, especially during the COVID-19 pandemic and considering Indonesia’s cultural context. Methods: This study utilized a cross-sectional design, and involved patients at the Gynecology and Colposcopy Clinic of Dr. Cipto Mangunkusumo General Hospital. The estimated sample size was 48, determined using a diagnostic test formula. The sample population consisted of female patients with positive VIA or abnormal Pap smear results. Each patient underwent HPV DNA self-sampling and clinician sampling tests using the GenoFlow HPV Array technique and continued with colposcopy. All patients were also administered a questionnaire consisting of eight questions about their perspective on the self-sampling HPV DNA test. The data analysis employed a 2 × 2 table using SPSS version 20, and Cohen’s kappa coefficient was calculated to measure the agreement between the sampling results of patients’ and Clinicians’. Results: Among the examinations conducted by clinicians, there were 33 patients with positive HPV results, whereas through self-sampling, there were 28 patients with positive HPV (p=0.00). High risk HPV was the most commonly observed, with HPV type 16 appearing the most (15%). Based on these data, the self-sampling sensitivity, specificity, positive predictive value, and negative predictive value were 85%, 100%, 100%, and 75%, respectively, with a concordance rate of 89.6%. The Cohen’s Kappa coefficient between samples taken by the clinician and self-sampling resulted in K=0.778, which is considered a good agreement (K=0.61-0.80). All patients concluded that the procedure was easy (100%), and the majority (60.5%) expressed a preference for the self-sampling method. Conclusion: There is a good agreement between the results of self-sampling and clinician sampling for detecting HPV DNA, with patients positively accepting the self-sampling method, indicating its potential as an effective cervical cancer screening method. Keywords: Cervical Cancer Screening, Clinician Sampling, Human Papillomavirus, Self-Sampling.